Study of histomorphological spectrum of eyelid lesions - shrestha, Reshmi; Sayami, Gita (Journal of Pathology of Nepal, 2021)
Background: Eyelid pathologies are the most common surgical specimens encountered among all of the ophthalmic lesions and constitute a wide range of diseases by their unique histologic features. This study aims to find out the histopathological spectrum of eyelid lesions, their demographic distribution, and preferential location prevalent in our community. Materials and Methods: This is an observational study in which we retrospectively evaluated the data of 692 patients retrieved from the histopathology department of National Reference Laboratory, Kathmandu, from May 2016 to April 2019. Results: A total of 701 histologic diagnoses comprised of benign, precursor, and malignant lesions and accounted for 86.6%, 2.6%, and 10.8% respectively with preponderance in females. The common benign lesions included melanocytic nevus (17.7%), epidermal cyst (11%), hemangioma (8.9%), dermoid cyst (8.2%), chalazion (6.7%), and squamous papilloma (6.4%). Tumour of epidermal origin was the most common neoplastic lesion accounting for 31.2%. Basal cell carcinoma (50%) followed by sebaceous carcinoma (27.6%) and squamous cell carcinoma (14.5%) constituted the majority of malignant lesions prevalent above the age of 60 years with the preferential site of the upper eyelid for basal cell carcinoma and squamous cell carcinoma; and lower eyelid for sebaceous carcinoma. Conclusions: Benign eyelid lesions are more prevalent than malignant ones with overall female preponderance. Epidermal tumours are common among neoplasms. A malignant tumour, a disease of an elderly individual, is predominated by basal cell carcinoma followed by sebaceous carcinoma, an aggressive tumour with a high recurrence rate in our population.